Pengaruh Store Layout dan Motivasi Rasional terhadap Keputusan Pembelian Konsumen di Toko Abu Rohmah - Andara Selviranih; Siti Aidini Khoerunnisa; Hilda Sapitri; Ibnu Muhammad Sabilli; Muhammad Syehan; Nurul Aulia Fitriani (Pusat Riset dan Inovasi Nasional, 2025)
The purpose of this study is to investigate how customers' purchasing decisions at Abu Rohmah Store are influenced by store layout and rational motivation. The study uses a quantitative survey approach, gathering information from 50 respondents via questionnaires. Multiple linear regression analysis was used to examine the gathered data. The results indicate that store layout has a significant effect on consumers' purchasing decisions, with a regression coefficient of 0.814. Furthermore, customers' rational motivation is also significantly influenced by store layout, as evidenced by the regression coefficient of 0.347. According to the coefficient of determination, 64% of the variation in consumers' purchase decisions can be explained by these two variables. These results aid in the creation of marketing plans and the enhancement of offerings in the neighborhood retail industry.